Adaptatıon Of Sport Fanatıcısm Scale Into Turkısh - Erkan Faruk Şirin; Ali Erdoğan (Selcuk University, 2021)
Sometimes positive and sometimes negative meanings can be attributed to fanaticism in sports. In addition to the fact that fanatics, which are very attractive for sports marketers, are valuable customers of a brand, whereas social identity, relationship, and self-esteem researchers see fanaticism as a social endorsement, they also see extreme behaviors, including violence, as socially unacceptable. This study, which was carried out due to the need for a valid and reliable measurement tool to measure sports fanaticism for these different fields of study, aims to determine the validity and reliability of the Sport Fanaticism Scale developed by Dwyer, LeCrom and Greenhalgh (2018) in Turkish conditions. The 5-point Likert type scale consisting of 12 items was applied to 528 participants who are supporters of Besiktas, Fenerbahce, Galatasaray and Trabzonspor clubs. Confirmatory factor analysis (CFA) was conducted to examine the four-factor structure of the scale. It was observed that the values of fit indices are at good or excellent level in all parameters (χ²/sd= 2.81); RMSEA=.058; GFI=.96; CFI=.95; IFI=.95; AGFI =.93). The results show that the 12-item scale is consistent with the original four-factor structure and is compatible with the data. For the reliability of the scale, the internal consistency coefficients of the entire scale and its sub-dimensions were checked. In addition, Cronbach's Alpha and AVE and CR values were also calculated within the scope of the internal consistency reliability of the scale and the coefficients were found to be sufficient. Test-retest reliability analysis of the scale was also performed at three-week intervals. In the light of these findings, it was concluded that the "Sports Fanaticism Scale" is a valid and reliable measurement tool that is compatible with the Turkish cultural structure.